Application of solid waste ash as petroleum coke gasification catalyst, petroleum coke gasification method

CN115651707BActive Publication Date: 2026-10-30HUAZHONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211375461.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-04
Publication Date
2026-10-30
Estimated Expiration
2042-11-04

AI Technical Summary

Technical Problem

然而目前针对固体废弃物灰对石油焦气化催化作用研究较少,如能够将固体废弃物灰作为石油焦掺混对象加强石油焦气化反应性,利用“以废治废”方法可实现资源的综合利用

Benefits of technology

[0014]1、本发明的固体废弃物灰对石油焦气化催化作用明显,尤其当气化温度高于固体废弃物制备灰流动温度时,气化产物中产生的灰焦颗粒物有助于焦炭碳晶结构向无序化方向发展,且低熔融特征温度的灰有利于灰焦颗粒物的形成,进而促进石油焦气化反应;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115651707B_ABST
    Figure CN115651707B_ABST
Patent Text Reader

Abstract

The application provides application of solid waste ash as a petroleum coke gasification catalyst and a petroleum coke gasification method.The application of the solid waste ash as the petroleum coke gasification catalyst, the solid waste ash comprises at least one of city life garbage ash, garbage derived fuel ash, waste wood ash, city life garbage high-temperature combustion ash and city life garbage high-temperature gasification ash.The application further provides a petroleum coke gasification method, which comprises: mixing the solid waste ash with the petroleum coke, and carrying out a gasification reaction under normal pressure, with carbon dioxide as a gasification agent and at a high temperature of 1000-1300 DEG C.The solid waste ash has obvious catalytic effect on the petroleum coke gasification, especially when the gasification temperature is higher than the solid waste ash preparation ash flow temperature, the ash coke particulate matter generated in the gasification product is helpful for the development of the coke carbon crystal structure in the direction of disorder, and the ash with a low melting characteristic temperature is beneficial to the formation of the ash coke particulate matter, thereby promoting the petroleum coke gasification reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of petroleum coke gasification technology, and in particular to the application of solid waste ash as a petroleum coke gasification catalyst and a petroleum coke gasification method. Background Technology

[0002] Researchers have been studying the co-gasification of petroleum coke with coal and biomass, aiming to leverage the inherent properties of coal and biomass (minerals in ash or hydroxyl groups in volatile matter) to enhance the gasification reactivity of petroleum coke. Currently, the generation of solid waste is continuously increasing, making its incineration and resource utilization a hot topic. Through incineration, the organic components of solid waste are fully oxidized, while the inorganic components form slag and fly ash. However, there is limited research on the catalytic effect of solid waste ash on petroleum coke gasification. If solid waste ash could be used as a blending agent to enhance the gasification reactivity of petroleum coke, the comprehensive utilization of resources could be achieved through a "waste-to-waste" approach. Summary of the Invention

[0003] In view of this, the present invention proposes an application of solid waste ash as a catalyst for petroleum coke gasification and a petroleum coke gasification method to enhance the petroleum coke gasification reaction.

[0004] In a first aspect, the present invention provides an application of solid waste ash as a catalyst for petroleum coke gasification, wherein the solid waste ash includes at least one of municipal solid waste ash, waste-derived fuel ash, waste wood ash, high-temperature combustion ash of municipal solid waste, and high-temperature gasification ash of municipal solid waste.

[0005] Preferably, in the aforementioned application, the municipal solid waste ash comprises the following components by mass fraction: Fe2O3 1.40–1.50%, CaO 29.74–29.84%, SiO2 41.72–41.82%, Al2O3 9.54–9.64%, MgO 1.12–1.22%, Na2O 1.17–1.27%, K2O 5.02–5.12%, P2O5 5.90–6.00%, SO3 3.12–4.12%, TiO2 0.68–0.78%, and Cr2O3 0.04–0.14%.

[0006] Preferably, in the aforementioned application, the waste-derived fuel ash comprises the following components by mass fraction: Fe2O3 4.26–4.36%, CaO 44.20–44.30%, SiO2 30.58–30.68%, Al2O3 9.41–9.51%, MgO 0.88–0.98%, Na2O 3.39–3.49%, K2O 0.82–0.92%, P2O5 1.73–1.83%, SO3 1.55–1.65%, TiO2 2.17–2.27%, and Cr2O3 0.46–0.56%.

[0007] Preferably, in the aforementioned application, the waste wood ash comprises the following components by mass fraction: Fe2O3 6.69–6.79%, CaO 5.85–5.95%, SiO2 71.58–71.68%, Al2O3 7.96–8.06%, MgO 1.16–1.26%, Na2O 0.97–1.07%, K2O 1.96–2.06%, P2O5 1.75–1.85%, SO3 0.72–0.82%, TiO2 0.32–0.42%, and Cr2O3 0.49–0.59%.

[0008] Preferably, in the aforementioned application, the high-temperature combustion ash of municipal solid waste comprises the following components by mass fraction: Fe2O3 4.13–4.23%, CaO 30.41–30.51%, SiO2 47.24–47.34%, Al2O3 9.71–9.81%, MgO 0.02–0.12%, K2O 0.86–0.96%, P2O5 6.10–6.20%, TiO2 1.07–1.17%, and Cr2O3 0.01–0.11%.

[0009] Preferably, in the aforementioned application, the high-temperature gasification ash of municipal solid waste comprises the following components by mass fraction: Fe2O3 7.64–7.74%, CaO 31.98–32.08%, SiO2 39.85–39.95%, Al2O3 12.86–12.96%, MgO 0.07–0.17%, K2O 1.11–1.21%, P2O5 4.31–4.41%, TiO2 1.71–1.81%, and Cr2O3 0.02–0.12%.

[0010] Secondly, the present invention also provides a method for petroleum coke gasification, comprising the following steps:

[0011] The solid waste ash is mixed with petroleum coke and then gasified at atmospheric pressure with carbon dioxide as the gasifying agent at a temperature of 1000–1300°C.

[0012] Preferably, in the petroleum coke gasification method, the mass of the solid waste ash is 1 to 15% of the sum of the mass of petroleum coke and the mass of solid waste ash.

[0013] The application of solid waste ash as a catalyst in petroleum coke gasification and the petroleum coke gasification method of the present invention have the following advantages compared with the prior art:

[0014] 1. The solid waste ash of the present invention has a significant catalytic effect on petroleum coke gasification. In particular, when the gasification temperature is higher than the flow temperature of the solid waste ash, the ash coke particles generated in the gasification products help the carbon crystal structure of coke to develop towards disorder, and the ash with a low melting characteristic temperature is conducive to the formation of ash coke particles, thereby promoting the petroleum coke gasification reaction.

[0015] 2. Under the catalytic effect of municipal solid waste ash, the trend of petroleum coke gasification towards an ordered structure at 1100℃ was controlled, while the gasified coke was promoted towards a disordered structure. The catalytic effect accelerated the disordered development of petroleum coke carbon crystal structure, and the combination of coke and molten ash particles to form ash-coke particles played a further catalytic role in the gasification process.

[0016] 3. At 1000℃, the catalytic effect of municipal solid waste ash mainly enhances the conversion of oxygen-containing functional groups on the surface of gasified coke to hydroxyl groups, achieving the best gasification effect when the ash ratio is 5%. At 1300℃, the catalytic effect of ash mainly enhances the decomposition of hydroxyl groups, and the co-gasification reaction index can reach 90.2% when the ash ratio is 3%. However, excessive ash will inhibit the co-gasification reaction.

[0017] 4. For the preparation of ash from municipal solid waste under different thermal conditions, the ash flow temperature is positively correlated with the co-gasification reaction index. The linear relationship between the ash flow temperature and the co-gasification reaction index is: CRI = 0.073FT + 9.4076, and the correlation coefficient R is... 2 At a value above 0.99, the effect of ash on the catalytic effect of petroleum coke gasification can be determined by detecting the flow temperature of the ash. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 A graph showing the co-gasification reaction index of petroleum coke JSP and MA1;

[0020] Figure 2 SEM images of JSP and MA1 co-gasified coke from petroleum coke at 1000 and 1300℃;

[0021] Figure 3 Fourier transform infrared spectra of petroleum coke JSP and co-gasified coke of petroleum coke JSP and MA1 at 1000-1300℃.

[0022] Figure 4 Figures showing the co-gasification reaction index of petroleum coke and MA1 in different proportions;

[0023] Figure 5 Fourier transform infrared spectra of coke co-gasified with petroleum coke and MA1 at different ratios at 1000℃;

[0024] Figure 6 Fourier transform infrared spectra of coke co-gasified with petroleum coke and MA1 at 1300℃ with different proportions.

[0025] Figure 7 XRD patterns of MA1, RA1, WA1, MA2, and MA3;

[0026] Figure 8 A graph showing the cogasification index of five types of solid waste ash and petroleum coke;

[0027] Figure 9 The graph shows a linear relationship between the flow temperature of ash and the co-gasification reaction index.

[0028] Figure 10 Fourier transform infrared spectra of co-gasified coke from petroleum coke and five kinds of solid waste ash at 1300℃. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0030] This application provides an application of solid waste ash as a catalyst for petroleum coke gasification. The solid waste ash includes at least one of municipal solid waste ash, waste-derived fuel ash, waste wood ash, high-temperature combustion ash of municipal solid waste, and high-temperature gasification ash of municipal solid waste.

[0031] In some embodiments, municipal solid waste ash comprises the following components by mass fraction: Fe2O3 1.40–1.50%, CaO 29.74–29.84%, SiO2 41.72–41.82%, Al2O3 9.54–9.64%, MgO 1.12–1.22%, Na2O 1.17–1.27%, K2O 5.02–5.12%, P2O5 5.90–6.00%, SO3 3.12–4.12%, TiO2 0.68–0.78%, and Cr2O3 0.04–0.14%.

[0032] The solid waste ash of this application has a significant catalytic effect on petroleum coke gasification. In particular, when the gasification temperature is higher than the flow temperature of the solid waste ash, the ash coke particles generated in the gasification products help the carbon crystal structure of coke to develop towards disorder. Furthermore, ash with a low melting characteristic temperature is conducive to the formation of ash coke particles, thereby promoting the petroleum coke gasification reaction.

[0033] In some embodiments, the waste-derived fuel ash comprises the following components by mass fraction: Fe2O3 4.26–4.36%, CaO 44.20–44.30%, SiO2 30.58–30.68%, Al2O3 9.41–9.51%, MgO 0.88–0.98%, Na2O 3.39–3.49%, K2O 0.82–0.92%, P2O5 1.73–1.83%, SO3 1.55–1.65%, TiO2 2.17–2.27%, and Cr2O3 0.46–0.56%.

[0034] In some embodiments, waste wood ash comprises the following components by mass fraction: Fe2O3 6.69–6.79%, CaO 5.85–5.95%, SiO2 71.58–71.68%, Al2O3 7.96–8.06%, MgO 1.16–1.26%, Na2O 0.97–1.07%, K2O 1.96–2.06%, P2O5 1.75–1.85%, SO3 0.72–0.82%, TiO2 0.32–0.42%, and Cr2O3 0.49–0.59%.

[0035] In some embodiments, the high-temperature combustion ash of municipal solid waste comprises the following components by mass fraction: Fe2O3 4.13–4.23%, CaO 30.41–30.51%, SiO2 47.24–47.34%, Al2O3 9.71–9.81%, MgO 0.02–0.12%, K2O 0.86–0.96%, P2O5 6.10–6.20%, TiO2 1.07–1.17%, and Cr2O3 0.01–0.11%.

[0036] In some embodiments, the high-temperature gasification ash of municipal solid waste comprises the following components by mass fraction: Fe2O3 7.64–7.74%, CaO 31.98–32.08%, SiO2 39.85–39.95%, Al2O3 12.86–12.96%, MgO 0.07–0.17%, K2O 1.11–1.21%, P2O5 4.31–4.41%, TiO2 1.71–1.81%, and Cr2O3 0.02–0.12%.

[0037] Based on the same inventive concept, this application also provides a method for petroleum coke gasification, including the following steps:

[0038] The solid waste ash described above is mixed with petroleum coke and gasified under normal pressure at a temperature of 1000–1300°C using carbon dioxide as the gasifying agent. In some embodiments, the mass of the solid waste ash is 1–15% of the sum of the mass of the petroleum coke and the mass of the solid waste ash.

[0039] In some embodiments, an excess of carbon dioxide vaporizing agent is maintained during the vaporization reaction.

[0040] The following specific embodiments further illustrate the application of solid waste ash as a catalyst in petroleum coke gasification and the petroleum coke gasification method. This section further illustrates the content of the present invention in conjunction with specific embodiments, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in the art.

[0041] The petroleum coke JSP used in the following examples was provided by Sinopec Shanghai Jinshan Petroleum Branch. The petroleum coke gasification reaction experiment was conducted on an electrically heated vertical drop tube furnace gasification unit (see the inventor's published paper: "Effect of the Composition of Additive Ash on the Thermal Behavior of Petroleum Coke Ash during Gasification, The fate of char structure and active groups in petroleum coke gasification in a drop tube furnace"). Solid waste ash was also selected as the research object to explore its influence on the catalytic mechanism of petroleum coke gasification. Typical solid waste came from the Enerkem waste treatment plant in Edmonton, Alberta, Canada, and the sample types included: municipal solid waste (MSW), waste-derived fuel (RDF), and waste wood (WW). The industrial and elemental analysis results of the three typical solid wastes are shown in Table 1. Municipal solid waste ash (MA1), waste-derived fuel ash (RA1), and waste wood ash (WA1) were prepared according to the Chinese method for determining the composition of solid biomass fuel ash (GB / T30725-2014). (The ash remaining after measuring the ash content using the method in GB / T30725-2014 is the prepared ash.) Furthermore, municipal solid waste high-temperature combustion ash (MA2), municipal solid waste, and high-temperature gasification ash (MA3) were prepared by reacting for 2 seconds in air and CO2 atmospheres at 1300℃ using a drip furnace and a single-particle feed device. In the following examples, the gasification reaction time was 2 seconds.

[0042] Table 1 - Industrial and Elemental Analysis of Typical Solid Wastes

[0043]

[0044] a Subtraction

[0045] The composition of municipal solid waste ash (MA1), waste-derived fuel ash (RA1), waste wood ash (WA1), municipal solid waste high-temperature combustion ash (MA2), municipal solid waste and high-temperature gasification ash (MA3) used in the following examples is shown in Table 2 below.

[0046] Table 2 - XRF analysis results (wt%) of different solid waste ash

[0047]

[0048]

[0049] Example 1

[0050] This application also provides a method for petroleum coke gasification, including the following steps:

[0051] Municipal solid waste ash (MA1) and petroleum coke JSP are mixed evenly and then gasified under normal pressure with carbon dioxide as the gasifying agent at a temperature of 1000-1300℃ (gasification reaction is carried out at temperatures of 1000℃, 1100℃, 1200℃, and 1300℃ respectively) for 2 seconds. The mass of municipal solid waste ash (MA1) is 5% of the sum of the mass of petroleum coke JSP and the mass of municipal solid waste ash (MA1).

[0052] Following the method in Example 1, the co-gasification reaction index of petroleum coke JSP and MA1 is as follows: Figure 1 As shown. Figure 1 JSP in Chinese means the gasification reaction under the same conditions without the addition of MA1.

[0053] from Figure 1 As can be seen, the co-gasification reaction index increases continuously with increasing temperature, indicating that the addition of MA1 has a significant catalytic effect on petroleum coke. At 1000℃, MA1 nearly doubled the petroleum coke gasification reaction index; the increase in the co-gasification reaction index (62.7%) was relatively small when the temperature rose to 1100℃; however, as the temperature increased to 1200℃, the co-gasification reaction index (70.2%) increased significantly; and at 1300℃, the co-gasification reaction index further increased to 83.1%. Under the catalytic effect of MA1, the gasification reactivity of petroleum coke is enhanced, and the co-gasification reaction index is greatly increased. When the temperature reaches 1200℃, the co-gasification reaction index increases significantly, suggesting that the flow temperature of MA1 ash is below 1200℃, and the ash melting behavior of MA1 acts on the petroleum coke gasification reaction, producing a further catalytic effect. The ash melting behavior of petroleum coke is conducive to enhancing the gasification reaction.

[0054] Figure 2SEM images of co-gasified coke (i.e., solid products after gasification) of petroleum coke JSP and MA1 at 1000 and 1300℃ were analyzed comparatively. At 1000℃, small ash particles (<10μm) appeared in the co-gasification products, and the coke product size was relatively large, with a large number of irregular fine particles adsorbed on the coke surface. However, at 1300℃, the ash particles in the gasification products increased in size, the coke breakage intensified, a large number of ash particles adhered to the coke surface, and the irregular fine particles decreased significantly. The gasified coke and molten ash particles combined to form ash coke particles. Previous analysis suggests that the flow temperature of MA1 ash is below 1200℃. Therefore, at 1300℃, a large number of molten ash particles were dispersed on the surface of the gasified coke. The mineral metal elements in these particles catalyzed the gasified coke surface, further enhancing the co-gasification reaction, resulting in increased coke breakage and a sharp decrease in irregular fine particles.

[0055] Table 3 compares and analyzes the carbon crystal structure characteristics of JSP gasification coke and JSP-blended MA1 co-gasification coke. This application utilizes Raman spectroscopy to detect the carbon crystal structure of petroleum coke and its gasification coke, and uses the Origin 9.1-PeakFitting function to perform peak separation on the Raman spectra. The Raman spectra are fitted to five characteristic peaks, namely G, D1, D2, D3, and D4 peaks, and the structural types represented by each characteristic peak are shown in Table 4. Raman spectral intensity and full width at half maximum (FWHM) are commonly used to characterize the microstructure of samples, but these two parameters depend on the intensity of the spectrum itself, making comparison between different spectra difficult. Therefore, this paper uses peak area as a combined parameter representing peak intensity and FWHM, and uses the peak area ratio as a characteristic parameter characterizing the carbon crystal structure.

[0056] In Table 3, I D1 / I G The value I is used to characterize the degree of disorder in the carbon crystal structure. D1 / I G A higher value indicates a higher degree of disorder in the carbon crystal structure and a lower degree of graphitization. The degree of disorder in the structure of carbonaceous fuels is closely related to their gasification reactivity. G / I ALL The value represents the degree of graphitization, that is, the degree of order in the carbon crystal structure. For example, I in carbonaceous fuels D1 / I G The smaller the value, the better. G / I ALL A higher value indicates a higher degree of order in the carbon crystal structure, and consequently, a lower reactivity. D3 and D4 represent the amorphous carbon structure and active sites, respectively. D3+D4 / I G The value represents the amorphous carbon structure and the content of active sites.

[0057] Table 3 - Characteristic parameters of carbon crystal structure of petroleum coke and MA1 co-gasified coke

[0058]

[0059] Table 4 - Melting characteristic parameters of different ashes

[0060] G band 1580 <![CDATA[E in the aromatic layer of graphite crystal 2g symmetric stretching vibration]]> <![CDATA[D1 band]]> 1350 <![CDATA[A in the plane of graphite crystal 1g symmetric vibration and heteroatom disordered structure vibration]]> <![CDATA[D2 band]]> 1620 lattice vibrations of graphene <![CDATA[D3 band]]> 1530 <![CDATA[sp in amorphous carbon 2 bond vibration]]> <![CDATA[D4 band]]> 1150 Vibration of non-graphite structures

[0061] As can be seen from Table 3, under the catalytic action of MA1, at 1000℃, the I of co-gasified coke... D1 / I G The value increases significantly, and the carbon crystal structure of the co-gasified coke develops towards disorder, causing the co-gasification reaction index to increase by nearly double compared to the JSP gasification reaction index. With increasing gasification temperature, I... D1 / I G The value increases slowly. As analyzed earlier, at 1200℃, the ash melting behavior of MA1 acts on the co-gasification reaction, promoting the Ig of the co-gasified coke. D1 / I G The value increases again, and the carbon crystal structure further develops towards disorder, leading to a significant increase in the co-gasification reaction index and further enhancing the catalytic effect of petroleum coke gasification. When the temperature rises to 1300℃, the Ig of the co-gasified coke... D1 / I G The value continued to increase, causing the co-gasification reaction index to rise to 83.1%. This is related to the I value of the carbon crystal structure of petroleum coke produced by JSP gasification. G / I ALL The values ​​of I, which first increase and then decrease, show different patterns. (The text also mentions petroleum coke JSP and MA1 co-gasified coke, but these appear unrelated to the main point about I.) G / I ALL The value decreases continuously with increasing temperature, indicating a decrease in the graphitization degree of the co-gasified coke carbon crystal structure. When the gasification temperature reaches 1200℃, the degree of disorder in the carbon crystal structure further changes. However, under the catalytic action of MA1, at 1100℃, the trend of petroleum coke gasification towards an ordered carbon crystal structure is controlled, and the gasified coke is promoted towards a disordered structure. This indicates that under the catalytic action of MA1, even at temperatures below 1200℃, the development of the carbon crystal structure towards disorder can be promoted, enhancing the reactivity of petroleum coke gasification. The Ig value of petroleum coke JSP and MA1 co-gasified coke... D3+D4 / I G The value increases with increasing temperature because the mineral metal elements catalyze the surface of the gasified coke, leading to a continuous increase in amorphous carbon and active sites in the co-gasified coke. When the gasification temperature is between 1000 and 1100℃, the Ig of the co-gasified coke... D3+D4 / I G The value increment is relatively small; however, at 1200–1300℃, the I value of co-gasified coke is... D3+D4 / IG The significant increase in the value further demonstrates that the ash melting behavior of MA1 can further enhance the catalytic effect, promote a substantial increase in amorphous carbon and active sites in gasified coke, and thus promote the development of disordered carbon crystal structure.

[0062] Table 5 compares and analyzes the specific surface area and pore structure characteristics of petroleum coke JSP gasification coke and petroleum coke JSP blended with MA1 co-gasification coke.

[0063] Table 5 - Specific surface area and pore structure characteristics of JSP and MA1 co-gasified petroleum coke

[0064]

[0065] As temperature increases, the specific surface area of ​​JSP gasified petroleum coke first increases and then decreases. When the temperature is below 1100℃, the volatile matter removal reaction promotes pore structure development and increases the specific surface area; at 1100℃, the specific surface area reaches its peak (14.584 m²). 2 ·g -1 Afterward, the pore structure development trend changed; when the temperature exceeded 1100℃, the petroleum coke gasification reaction was enhanced, and the coke gasification decomposition formed gasification products with underdeveloped pores. Under various gasification temperature conditions, the specific surface area of ​​co-gasified coke from petroleum coke JSP and MA1 was greater than that of coke from petroleum coke gasification. Furthermore, with increasing gasification temperature, the specific surface area of ​​co-gasified coke also showed a pattern of first increasing and then decreasing, but the peak value (21.216m) remained relatively constant. 2 ·g -1 The presence of a value at 1200℃ indicates that, under the catalytic action of MA1, the pore structure of the gasified coke continues to develop, increasing the gas-solid reaction area and thus enhancing the petroleum coke gasification reaction. Below 1200℃, the pore volume of JSP petroleum coke gasified coke remains essentially unchanged, indicating slow pore structure development; while the pore volume of co-gasified coke increases significantly, further demonstrating that MA1 can promote the continuous development of the petroleum coke pore structure. The average pore size of both petroleum coke and MA1 co-gasified coke tends to decrease with increasing gasification temperature, indicating that while MA1 catalysis promotes pore structure development, the relative content of micropores continuously increases.

[0066] Fourier transform infrared spectra of petroleum coke JSP and co-gasified coke of petroleum coke JSP and MA1 at 1000–1300℃ are as follows: Figure 3 As shown.

[0067] Under the catalytic action of MA1, the aliphatic symmetric and asymmetric methyl or methylene stretching vibration peaks, aromatic C=C stretching vibration peaks, and oxygen-containing functional group stretching vibration peaks of gasified coke are significantly weakened; however, at 1000℃, the hydroxyl stretching vibration peak is strengthened. Petroleum coke ash can enhance the conversion of oxygen-containing functional groups to hydroxyl groups. At 1000℃, the active metal elements in MA1 accelerate the conversion of oxygen-containing functional groups to hydroxyl groups on the surface of gasified coke, promoting the strengthening of the hydroxyl stretching vibration peak. Therefore, under the catalytic action of MA1, the conversion of oxygen-containing functional groups to hydroxyl groups in gasified coke, and the newly generated hydroxyl groups are conducive to the development of the carbon crystal structure towards disorder, accompanied by an increase in amorphous carbon and active sites, enhancing the reactivity of petroleum coke gasification. With the increase of co-gasification temperature, the catalytic action of MA1 promotes the continuous decomposition of the main functional groups of gasified coke, leading to a continuous weakening of the hydroxyl stretching vibration peak. At 1000℃, the addition of MA1 promotes the conversion of a large number of oxygen-containing functional groups in the gasified coke into hydroxyl groups. As the gasification temperature increases, the hydroxyl groups in the gasified coke cannot be replenished due to the excessive decomposition of these oxygen-containing functional groups. The consumption of hydroxyl groups exceeds the generation, resulting in a continuous weakening of the hydroxyl stretching vibration peak with increasing temperature. During petroleum coke gasification, the oxygen-containing functional groups are more reactive than hydroxyl radicals.

[0068] Example 2

[0069] This application also provides a method for petroleum coke gasification, including the following steps:

[0070] Municipal solid waste ash (MA1) and petroleum coke JSP were mixed evenly and then gasified under normal pressure with carbon dioxide as the gasifying agent at a temperature of 1000-1300℃ (the gasification reaction was carried out at temperatures of 1000℃ and 1300℃ respectively). The mass of municipal solid waste ash (MA1) was 1%, 3%, 5%, 10%, and 15% of the sum of the mass of petroleum coke JSP and the mass of municipal solid waste ash (MA1).

[0071] Following the method in Example 2, the co-gasification reaction index of different proportions of petroleum coke and MA1 is as follows: Figure 4 As shown.

[0072] At 1000℃, compared to JSP gasification, the co-gasification reaction index of petroleum coke and 1% MA1 increased by 22.6%. With increasing MA1 ratio, the co-gasification reaction index increased, reaching its peak at 5% MA1. Further increasing the MA1 ratio slightly decreased the co-gasification reaction index. At 1300℃, the co-gasification reaction index also showed a pattern of first increasing and then decreasing with increasing MA1 ratio, reaching its peak at 3% MA1. The petroleum coke gasification reaction is affected by ash content, ash composition, and ash fusibility; ash fusion behavior promotes petroleum coke gasification reactivity. At 1300℃, the fusion behavior of MA1 enhanced the catalytic effect of petroleum coke gasification, resulting in the peak co-gasification reaction index at 3% MA1. However, when the MA1 ratio exceeded 3%, the co-gasification reaction index decreased significantly, indicating that besides the catalytic effect of MA1 on petroleum coke, other factors inhibited the co-gasification reaction. For example, a large amount of molten ash may adhere to the surface of gasified coke, blocking the gas-solid reaction area, or passivate catalytically active minerals, leading to a decrease in the co-gasification reaction index. Therefore, at 1300°C, when the MA1 ratio is greater than 3%, the molten phase minerals reduce the co-gasification reaction index by blocking pores or passivating active minerals.

[0073] Table 6 compares and analyzes the carbon crystal structure characteristics of coke produced by JSP and MA1 co-gasification with different proportions of petroleum coke at 1000 and 1300℃.

[0074] Table 6 - Characteristic parameters of carbon crystal structure of coke produced by co-gasification of petroleum coke and MA1 with different proportions

[0075]

[0076] Table 6 shows that under the two temperature conditions, the I of co-gasified coke D1 / I G The value of MA1 initially increases and then decreases with increasing MA1 ratio, consistent with the trend of co-gasification reaction index. D1 / I G Value, I G / I ALL Value and I D3+D4 / I G The values ​​change with strong synchronicity; here, we take I as an example. D1 / I G The Ig value was used as the main characteristic parameter for analysis. At 1000℃, the Ig values ​​of different proportions of petroleum coke and MA1 co-gasified coke were analyzed. D1 / I G The value ranges from 7.06 to 8.30, which is significantly higher than that of petroleum coke gasification coke. D1 / I GThe values ​​indicate that MA1 catalyzes the development of disordered crystal structure in petroleum coke. At 1300℃, the Ig values ​​of co-gasified coke with different proportions of petroleum coke and MA1... D1 / I G The value ranges from 8.75 to 9.35, which is significantly higher than the I value of co-gasified coke at 1000℃. D1 / I G The value indicates that the melting behavior of MA1 further enhances the catalytic effect. Under the catalytic action of MA1, the amorphous carbon and active sites in petroleum coke increase, the graphitic carbon crystal structure transforms into an amorphous carbon structure, and various defect sites appear in the carbon crystal structure, promoting the gasification reaction. However, with the increase of the MA1 ratio, the development of the co-gasified coke carbon crystal structure towards disorder is inhibited, indicating that in addition to the catalytic effect of MA1 on petroleum coke, there are other influencing factors that inhibit the co-gasification reaction. It is worth noting that at 1000℃, when the MA1 ratio is 5%, the co-gasified coke carbon crystal structure I D1 / I G The value reached its peak (8.30), while at 1300℃, the co-gasified coke carbon crystal structure I was at a ratio of 3% MA1. D1 / I G The value reached a peak (9.35). Increasing the gasification temperature and a relatively small ash ratio can significantly promote the disordered development of the carbon crystal structure of gasified coke, further illustrating that increasing the gasification temperature can further enhance the catalytic effect of MA1. Previous analysis indicated that the flow temperature of MA1 ash is below 1200℃; therefore, at 1300℃, the ash melting behavior of MA1 further catalyzes the gasification of petroleum coke, thus explaining the above phenomenon. At 1300℃, the carbon crystal structure of co-gasified coke with MA1 ratios of 1% and 3% is shown in Figure I. D3+D4 / I G The value is significantly higher than when the MA1 ratio is greater than 3% (I). D3+D4 / I G The value indicates that a small amount of MA1 can significantly increase amorphous carbon and active sites in petroleum coke, while when the amount of MA1 blended is too large, other influencing factors inhibit the formation of amorphous carbon and active sites.

[0077] Table 7 compares and analyzes the specific surface area and pore structure characteristics of co-gasified coke with different proportions of petroleum coke and MA1 under conditions of 1000 and 1300℃.

[0078] Table 7 - Specific surface area and pore structure characteristics of petroleum coke and MA1 co-gasified coke with different proportions

[0079]

[0080]

[0081] As shown in Table 7, at 1000℃, compared to JSP gasification coke from petroleum coke, co-gasification coke with different proportions of petroleum coke and MA1 showed increased specific surface area and pore volume, indicating that the catalytic effect of MA1 promoted the development of the pore structure of the gasification coke, thereby increasing the gas-solid reaction area and enhancing the co-gasification reaction. At 1300℃, when the MA1 ash ratio was 1% and 3%, the specific surface area and pore volume of the co-gasification coke further increased, indicating that the ash melting behavior of MA1 further promoted the development of the pore structure of the gasification coke from petroleum coke. However, when the ash ratio was greater than 3%, the specific surface area and pore volume of the co-gasification coke decreased. As analyzed above, at 1300℃, when the MA1 ratio was greater than 3%, the molten phase minerals reduced the co-gasification reaction index by blocking pores or passivating active minerals. The ash melting behavior of MA1 further catalyzed the gasification of petroleum coke, indicating that the molten phase minerals did not passivate active minerals and had a further catalytic effect. Therefore, when the MA1 ratio is greater than 3%, it mainly reduces the specific surface area and pore volume by blocking the pore structure through molten phase minerals, thereby reducing the gas-solid reaction area and weakening the co-gasification reaction. Furthermore, at 1300℃, the average pore size of co-gasified coke with different proportions of petroleum coke and MA1 is significantly smaller than that of coke gasified from petroleum coke, indicating that the catalytic effect of MA1 mainly involves enhancing micropore development.

[0082] Figures 5-6Fourier transform infrared (FTIR) spectra of co-gasified coke with different proportions of petroleum coke and MA1 at 1000 and 1300 °C were compared and analyzed. At 1000 °C, the stretching vibration peaks of aliphatic symmetric and asymmetric methyl or methylene groups, aromatic C=C stretching vibration peaks, and oxygen-containing functional group stretching vibration peaks in the gasified coke were significantly weakened. The hydroxyl stretching vibration peak, however, showed a pattern of first increasing and then decreasing with increasing MA1 ratio, reaching its strongest at an MA1 ratio of 5%. This pattern is largely consistent with the variation of the reaction index of the co-gasification of petroleum coke and MA1. At 1000 °C, the active metal elements in MA1 accelerate the conversion of oxygen-containing functional groups to hydroxyl groups on the surface of the gasified coke. It can be deduced that at 1000 °C, the catalytic effect of MA1 mainly enhances the conversion of oxygen-containing functional groups to hydroxyl groups; a stronger hydroxyl stretching vibration peak indicates better gasification reactivity, with the optimal gasification effect achieved at an MA1 ratio of 5%. Due to the limited content of oxygen-containing functional groups in coke, further increasing the MA1 ratio cannot further enhance the conversion of oxygen-containing functional groups to hydroxyl groups. Under high-temperature gasification conditions, excessive ash ratio leads to pore blockage, reducing the gas-solid reaction area and thus inhibiting the full conversion of oxygen-containing functional groups to hydroxyl groups. This results in a slight decrease in the hydroxyl stretching vibration peak when the MA1 ratio exceeds 5%. Overall, at 1000℃, increasing the ash ratio is beneficial for enhancing the conversion of oxygen-containing functional groups to hydroxyl groups during co-gasification, thereby enhancing the reactivity of petroleum coke gasification. However, when the MA1 ratio exceeds 5%, excessive ash inhibits the petroleum coke gasification reaction. At 1300℃, the aliphatic symmetrical and asymmetric methyl or methylene stretching vibration peaks, aromatic C=C stretching vibration peaks, oxygen-containing functional group stretching vibration peaks, and hydroxyl stretching vibration peaks of gasified coke further weaken. However, with the increase of the MA1 ratio, the hydroxyl stretching vibration peak shows a pattern of first decreasing and then increasing. At 1000℃, a large number of oxygen-containing functional groups in the gasified coke transform into hydroxyl groups, leading to their extensive decomposition. Consequently, as the gasification temperature increases, the hydroxyl groups in the gasified coke cannot be replenished, resulting in a greater consumption of hydroxyl groups than their formation. It can be deduced that at 1300℃, the catalytic effect of MA1 primarily enhances the decomposition of hydroxyl groups. A weaker hydroxyl stretching vibration peak indicates better gasification reactivity, with the optimal gasification effect achieved at an MA1 ratio of 3%. Further increases in the MA1 ratio do not further enhance hydroxyl consumption, indicating that excessive ash inhibits the gasification reaction. Molten ash coats the surface of the gasified coke, reducing the contact between the coke surface structure and the gasifying agent, thus inhibiting the decomposition and transformation of functional groups.

[0083] Example 3

[0084] XRD analysis was performed on municipal solid waste ash (MA1), waste-derived fuel ash (RA1), waste wood ash (WA1), municipal solid waste high-temperature combustion ash (MA2), and municipal solid waste and high-temperature gasification ash (MA3). The results are as follows: Figure 7 As shown. Figure 7Among them, 1: SiO2; 2: CaCO3; 3: Ca5(PO)3(OH); 4: NaAlSi3 O8; 5: K2Ca(CO3)2; 6: CaSiO3; 7: NaCl; 8: Fe2O3.

[0085] from Figure 7 The results show that MA1 and RA1 are mainly composed of SiO2 and CaCO3, with the characteristic peak intensity of CaCO3 in RA1 being significantly greater than that in MA1. Both MA1 and RA1 also contain small amounts of K2Ca(CO3)2 and NaCl. Furthermore, MA1 and RA1 also contain CaSiO3 and NaAlSi3O8, respectively. Due to the high Si content in WA1, the SiO2 characteristic peak is particularly prominent. Compared to MA1 and RA1, Fe was found in WA1 in the form of Fe2O3, while no Fe crystalline substances were found in the other ash samples. MA2 and MA3 are ash prepared through high-temperature combustion and high-temperature gasification; the mineral elements mainly exist as amorphous, non-crystalline substances, with only a small amount of SiO2 detected.

[0086] The melting characteristics of ash refer to the temperature features of ash during its transformation from a solid to a liquid state at high temperatures, including softening, melting, and flow. These melting characteristics are crucial for determining fuel applications in the fuel industry and are one of the important indicators for fuel selection. The gasification reactivity of petroleum coke is related not only to its ash content and composition but also to its ash melting characteristics, with lower ash melting characteristic temperatures exhibiting more pronounced gasification reactivity. Therefore, ash melting characteristics have a significant impact on the petroleum coke gasification reaction. Table 8 shows the melting characteristic temperatures for five types of ash preparation. In Table 8, DT represents the deformation temperature, ST represents the softening temperature, HT represents the hemispherical temperature, and FT represents the flow temperature.

[0087] Table 8 - Melting characteristic parameters of different ashes

[0088]

[0089]

[0090] The flow temperature of MA1 ash is 1182℃, which verifies the previous hypothesis that the flow temperature of MA1 is below 1200℃. Therefore, when the gasification temperature is higher than the flow temperature of MA1, a large number of molten ash particles will be formed during the co-gasification process, which have good diffusion and contact capabilities; at the same time, the molten ash particles are rich in mineral metal elements, and the liquid metal molten salt can enhance the contact between ions, thereby greatly promoting the gasification reactivity of petroleum coke.

[0091] The flow temperatures of the five prepared ashes, from lowest to highest, are: MA3 < MA1 < MA2 < RA1 < WA1. The pH (R0) is typically used to determine the flow temperature. A / B The ash fusion property is determined by the following formula:

[0092]

[0093] Generally, the lower the acidity or alkalinity, the lower the ash melting characteristic temperature.

[0094] R AI R represents the alkali index, used to describe the catalytic efficiency of active minerals in ash. AI The calculation formula is as follows:

[0095]

[0096] R AI The ratio of the content of catalytically active AAEMs (Fe2O3, CaO, MgO, Na2O, and K2O) to the content of non-catalytic acidic oxides (SiO2 and Al2O3) in ash and the relative content M of ash in petroleum coke are used to determine the composition of petroleum coke. ASH (%) was calculated.

[0097] The characteristic melting temperatures of MA1, MA2, and MA3 ash prepared from municipal solid waste under different thermal conditions are similar, with differences not exceeding 30℃. The flow temperature from low to high is: MA3 < MA1 < MA2. For ash prepared from municipal solid waste under different thermal conditions, the pH range is 1.33–1.63, and the pH from low to high is: MA3 < MA1 < MA2, consistent with its flow temperature variation. For MA1, RA1, and WA1 ash prepared from typical solid waste, the flow temperature from low to high is: MA1 < RA1 < WA1, and the pH range is 0.79–4.74. However, the pH from low to high is: RA1 < MA1 < WA1, which does not match the pH flow temperature variation. Studies have shown that when the CaO mass fraction is greater than 35%, the characteristic melting temperature of coal ash increases with increasing CaO content. Existing research indicates that when the pH value is greater than 3.65, the characteristic ash melting temperature of coal ash increases significantly. It also points out that when the CaO content is greater than 30%, high-melting-point CaO monomers are formed in the ash. Therefore, the pH value of WA1 (4.74) greater than 3.65 significantly increases the characteristic ash melting temperature, resulting in the highest ash flow temperature. In RA1, the CaO content (44.25%) is much greater than 30%. Although its pH value is lower than MA1, the large amount of Ca components forms CaO monomers, leading to a higher characteristic ash melting temperature, making the flow temperature of RA1 higher than that of MA1.

[0098] Example 4

[0099] This application also provides a method for petroleum coke gasification, including the following steps:

[0100] One of the following will be mixed evenly with petroleum coke JSP: municipal solid waste ash (MA1), waste-derived fuel ash (RA1), waste wood ash (WA1), municipal solid waste high-temperature combustion ash (MA2), municipal solid waste and high-temperature gasification ash (MA3), and then gasified at 1300℃ under normal pressure with carbon dioxide as the gasifying agent. The mass of MA1 / RA1 / WA1 / MA2 / MA3 is 5% of the mass of petroleum coke JSP and the sum of the masses of MA1 / RA1 / WA1 / MA2 / MA3, respectively.

[0101] In the above embodiments, MA1, RA1, WA1, MA2, and MA3 were thoroughly mixed with 95% JSP at a mass fraction of 5%, and a co-gasification experiment was completed at 1300°C. The co-gasification indices of the five prepared ash and petroleum coke were as follows: Figure 8 As shown. Figure 8 JSP in Chinese refers to the gasification reaction of petroleum coke under the same conditions without the addition of solid waste ash.

[0102] from Figure 8 It can be seen that all five types of solid waste ash have a significant promoting effect on the gasification reactivity of petroleum coke. Among them, WA1 has the weakest catalytic effect on petroleum coke gasification; compared with the JSP gasification reactivity index, the co-gasification index of WA1 and petroleum coke only increases by 24%. MA3 has the strongest catalytic effect on petroleum coke gasification; under the catalytic effect of MA3, the co-gasification index increases by 47%. The order of the catalytic effect of the five ash on petroleum coke gasification reaction from weakest to strongest is: WA1 <RA1<MA2<MA1<MA3。

[0103] The alkali index of the five types of ash is not directly related to their catalytic effect on petroleum coke gasification. For RA1, it has the highest alkali index, but its catalytic effect is relatively poor. Ash composition analysis shows that RA1 contains a large amount of CaO. During the ash preparation process at 550℃, CaO reacts with CO2 to form a large amount of CaCO3. However, during the high-temperature gasification process at 1300℃, CaCO3 decomposes to form high-melting-point CaO, increasing the ash melting characteristic temperature of RA1 and reducing its fluidity. The contact between the active metal elements in RA1 and the coke surface is limited, thus resulting in poor catalytic effect. For WA1, on the one hand, when the pH is greater than 3.65, the ash melting characteristic temperature increases significantly, and the ash flow temperature reaches as high as 1496℃, far exceeding the gasification temperature (1300℃), suggesting that the yield of molten ash particles in its co-gasification products is relatively low; on the other hand, WA1 has the lowest alkali index and the lowest proportion of active metal elements. These two factors combined result in the worst catalytic effect for WA1.

[0104] Mineral composition analysis shows that MA2 and MA3 are mainly composed of amorphous, non-crystalline substances, while MA1, RA1, and WA1 are mainly in crystalline form. Since MA2 and MA3 are ash produced by high-temperature combustion and high-temperature gasification, most of the alkali metals Na and K have volatilized during the ash production process. It can be deduced that the mineral composition of the ash is not closely related to the catalytic effect, and the catalytic effect of alkali metals Na and K on the petroleum coke gasification reaction is limited.

[0105] Analysis of the fusibility of ash revealed that the flow temperatures of the five ash types, from lowest to highest, followed the pattern: MA3 < MA1 < MA2 < RA1 < WA1. This pattern was negatively correlated with the variation of the co-gasification reaction index of the five ash types and petroleum coke. In other words, the characteristic fusibility temperature of gasification ash was negatively correlated with its catalytic effect on petroleum coke gasification; petroleum coke gasification reactivity was more pronounced at lower ash fusibility temperatures. Similarly, ash from solid waste with lower ash fusibility temperatures was beneficial for enhancing petroleum coke gasification reactivity because the co-gasification process could form a large number of molten ash particles. This product has good diffusion and contact capabilities, and is rich in mineral metal elements. The liquid metal molten salt can enhance the contact between ions, promoting petroleum coke gasification reactivity. Therefore, the gasification reactivity of petroleum coke is not only related to its mineral content and composition, but ash fusibility also plays a crucial role in promoting petroleum coke gasification reactivity.

[0106] For the preparation ash MA1, MA2, and MA3 from municipal solid waste under different thermal conditions, the flow temperature of the ash shows a linear relationship with the co-gasification reaction index, with a correlation coefficient R. 2 Above 0.99, such as Figure 9 As shown. The catalytic effect of ash on the petroleum coke gasification reaction can be determined by detecting the flow temperature of the ash. The relationship between the ash flow temperature and the co-gasification reaction index is: CRI = 0.073FT + 9.4076. The alkali index of ash prepared from municipal solid waste under different thermal conditions also shows a linear relationship with the co-gasification reaction index, with the relationship being: CRI = 0.18R. AI The correlation coefficient (0.86) is lower than that of the linear relationship between the ash flow temperature and the co-gasification reaction index (0.99). Therefore, judging the catalytic effect of municipal solid waste ash on petroleum coke gasification reaction by its flow temperature is more appropriate. The main factor affecting the reactivity of petroleum coke gasification is the diffusion capacity of coal ash rather than the form of active metal elements. This is because when ash exists in fluid form, it can promote the freedom of active metal elements and increase the contact points between the catalyst and the coke surface. MA3 has the lowest ash flow temperature and the highest alkali index. Both factors jointly promote the petroleum coke gasification reaction, making its co-gasification reaction index with petroleum coke the highest. For MA1, RA1, and WA1 prepared from typical solid waste, their flow temperature and co-gasification reaction index have poor linear correlation coefficients.2 is only 71%, as Figure 9 shown. Since the flow temperature of WA1 (1496°C) is much higher than the gasification temperature (1300°C), its poor flowability may be the main reason leading to their poor correlation coefficient.

[0107] Table 9 comparatively analyzes the characteristic parameters of the carbon crystal structure of co-gasification coke of petroleum coke and five types of solid waste ash at 1300°C.

[0108] Table 9 - Characteristic parameters of carbon crystal structure of co-gasification coke of different blended ash and petroleum coke at 1300°C

[0109]

[0110]

[0111] It can be seen from Table 9 that the I D1 / I G value follows the order: WA1<RA1<MA2<MA1<MA3, which is consistent with the variation law of the co-gasification reaction index but opposite to the variation law of the flow temperature of the five blended ashes, indicating that ash with higher flowability is conducive to the development of gasification coke toward the disordered direction of the carbon crystal structure. The I G / I ALL value variation law of the carbon crystal structure of co-gasification coke is exactly opposite to that of the I D1 / I G value, and the disordered development of the carbon crystal structure continuously reduces the graphitization degree of the carbon crystal structure. The I D3+D4 / I G value of the co-gasification coke of petroleum coke and WA1 is significantly smaller than that of the other four blended ashes. When the flow temperature of WA1 is much higher than the gasification temperature, its catalytic effect is relatively low, resulting in fewer amorphous carbon and active sites in the gasification coke; while the flow temperature of the other four blended ashes is lower than the gasification temperature, the stronger catalytic effect promotes the increase of amorphous carbon and active sites in the gasification coke. It can be inferred that the flowability of ash is conducive to strengthening the contact degree of active metal elements in ash with the coke surface, increasing the number of amorphous carbon and active sites, and promoting the gasification reaction of petroleum coke.

[0112] Table 10 comparatively analyzes the characteristic parameters of specific surface area and pore structure of co-gasification coke of petroleum coke and five types of prepared ash at 1300°C.

[0113] Table 10 - Characteristic parameters of specific surface area and pore structure of co-gasification coke of different blended ash and petroleum coke

[0114]

[0115] As can be seen from Table 10, the order of specific surface area from small to large is: WA1<RA1<MA2<MA1<MA3, which is consistent with the co-gasification reaction index I of the five mixed ashes and petroleum coke D1 / I G value and I D3+D4 / I G value, but opposite to the flow temperature rule of the five prepared ashes, indicating that ash with high fluidity is beneficial to the increase of the specific surface area of gasified coke. At a gasification temperature of 1300℃, the pore volume of the coke obtained from co-gasification of petroleum coke and five prepared ashes ranges from 0.032 to 0.035, with a small difference in pore volume change, while the average pore diameter of MA3, which has the largest specific surface area, is significantly lower than that of the other four mixed ashes, indicating that high-fluidity ash promotes the development of micropores in gasified coke. Therefore, the high-fluidity ash flows and diffuses freely on the surface of petroleum coke, strengthens the contact between active metal elements and the surface of petroleum coke to generate a large number of active sites, promotes the transformation of graphitized carbon crystal structure to disordered carbon crystal structure, accompanied by the generation of amorphous carbon; at the same time, it also promotes the development of pore structure and enhances the gasification reaction of petroleum coke. Therefore, the catalytic effect of high-fluidity ash promotes the development of pore structure, especially the development of micropores, thereby further promoting gasification reactivity.

[0116] Figure 10 The Fourier transform infrared spectra of the coke obtained from co-gasification of petroleum coke and five prepared ashes at 1300℃ were comparatively analyzed.

[0117] Under the catalytic action of the five prepared ashes, the aliphatic symmetric and asymmetric methyl or methylene stretching vibration peaks, aromatic C=C stretching vibration peaks, oxygen-containing functional group stretching vibration peaks and hydroxyl stretching vibration peaks of the gasified coke are all significantly weakened. At 1300℃, the catalytic effect of MA1 is mainly to strengthen the decomposition of hydroxyl groups, and the weaker the hydroxyl stretching vibration peak, the better the co-gasification reactivity. Under the catalytic action of WA1, the hydroxyl stretching vibration peak of the co-gasified coke is the strongest, followed by RA1, and the hydroxyl stretching vibration peaks of MA1, MA2 and MA3 are similar and relatively weak. Compared with the gasification of petroleum coke alone, the overall amplitude change of functional groups of the coke obtained from co-gasification of petroleum coke with MA1, MA2 and MA3 follows the rule: MA2<MA1<MA3. In the case where the hydroxyl stretching vibration peaks of the co-gasified coke of MA1, MA2 and MA3 are similar, the catalytic effect of MA3 has the strongest degree of conversion of oxygen-containing functional groups to hydroxyl groups, indicating that the gasification decomposition of the supplemented hydroxyl groups is also the most intense. It can be inferred that the catalytic effect of MA3 is most favorable to the gasification decomposition of hydroxyl groups. Similarly, the catalytic effect of MA2 has the weakest effect on the gasification decomposition of hydroxyl groups, and MA1 is in the middle. Therefore, at 1300℃, the order of hydroxyl consumption of the coke obtained from co-gasification of petroleum coke and five prepared ashes from less to more is: WA1<RA1<MA2<MA1<MA3, which is consistent with the co-gasification reaction index, specific surface area, I of petroleum coke and five prepared ashes D1 / I GValue and I D3+D4 / I G The values ​​showed a consistent pattern and were negatively correlated with the flow temperature changes of the five blended ashes, indicating that highly fluid ash is conducive to the gasification and decomposition of hydroxyl groups.

[0118] In summary, the transformation and decomposition of oxygen-containing functional groups and hydroxyl groups play an important role in the co-gasification process of solid waste ash and petroleum coke. At 1000℃, the catalytic effect of ash is mainly to enhance the transformation of oxygen-containing functional groups on the surface of gasified coke into hydroxyl groups; at 1300℃, the catalytic effect of ash is mainly to enhance the gasification and decomposition of hydroxyl groups on the surface of gasified coke.

[0119] This application used typical solid waste ash to study the catalytic mechanism of petroleum coke gasification on a drip-tube gasification experimental device, focusing on the effects of temperature, ash content, and ash properties. The physicochemical characteristics of the gasification products were analyzed using scanning electron microscopy, specific surface area and pore size analyzer, laser confocal Raman spectroscopy, and Fourier transform infrared spectroscopy, revealing the catalytic mechanism of petroleum coke gasification. The main conclusions are as follows:

[0120] (1) Under the catalytic effect of municipal solid waste ash, the trend of petroleum coke gasification coke towards an ordered structure at 1100℃ was controlled, and the gasification coke was promoted towards a disordered structure. The catalytic effect promoted the development of petroleum coke carbon crystal structure towards disorder in advance, and the combination of coke and molten ash particles to form ash coke particles played a further catalytic role in the gasification process.

[0121] (2) At 1000℃, the catalytic effect of municipal solid waste ash is mainly to enhance the conversion of oxygen-containing functional groups on the surface of gasified coke to hydroxyl groups, and the best gasification effect is achieved when the ash ratio is 5%. At 1300℃, the catalytic effect of ash is mainly to enhance the decomposition of hydroxyl groups, and the co-gasification reaction index can reach 90.2% when the ash ratio is 3%. However, excessive ash will inhibit the co-gasification reaction.

[0122] (3) When the gasification temperature is higher than the ash flow temperature, ash melting behavior plays a key role in the petroleum coke gasification reaction. Highly fluid ash, through its flow and diffusion on the surface of petroleum coke, enhances the contact between active metal elements and the surface of petroleum coke, generating a large amount of amorphous carbon and active sites, promoting the development of graphitized carbon crystal structure towards disorder, thereby promoting the gasification reaction. At the same time, the catalytic effect of highly fluid ash promotes the development of pore structure, especially micropores.

[0123] (4) For the preparation of ash from municipal solid waste under different thermal conditions, the flow temperature of the ash is positively correlated with the co-gasification reaction index. The linear relationship between the flow temperature of the ash and the co-gasification reaction index is: CRI = 0.073FT + 9.4076, and the correlation coefficient R 2At a value above 0.99, the effect of ash on the catalytic effect of petroleum coke gasification can be determined by detecting the flow temperature of the ash.

[0124] (5) Solid waste ash has a significant catalytic effect on petroleum coke gasification. Especially when the gasification temperature is higher than the flow temperature of solid waste ash, the ash and coke particles generated in the gasification products help the carbon crystal structure of coke to develop towards disorder. Moreover, ash with a low melting characteristic temperature is conducive to the formation of ash and coke particles, thereby promoting the petroleum coke gasification reaction. The melting characteristic temperature of ash can be used as a basis for selecting solid waste ash to be blended with petroleum coke.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for petroleum coke gasification, characterized in that, Includes the following steps: Solid waste ash is mixed with petroleum coke and gasified at 1300℃ under normal pressure using carbon dioxide as a gasifying agent. The mass of the solid waste ash is 3% of the sum of the mass of petroleum coke and the mass of solid waste ash; The solid waste ash is municipal solid waste ash, which comprises the following components by mass fraction: Fe2O3 1.40~1.50%, CaO 29.74~29.84%, SiO2 41.72~41.82%, Al2O3 9.54~9.64%, MgO 1.12~1.22%, Na2O 1.17~1.27%, K2O 5.02~5.12%, P2O5 5.90~6.00%, SO3 3.12~4.12%, TiO2 0.68~0.78%, and Cr2O3 0.04~0.14%. Alternatively, solid waste ash can be mixed with petroleum coke and gasified at 1300°C under normal pressure using carbon dioxide as a gasifying agent; the mass of the solid waste ash is 5% of the sum of the mass of petroleum coke and the mass of solid waste ash. The solid waste ash is high-temperature gasification ash from municipal solid waste, comprising the following components by mass fraction: Fe2O3 7.64~7.74%, CaO 31.98~32.08%, SiO2 39.85~39.95%, Al2O3 12.86~12.96%, MgO 0.07~0.17%, K2O 1.11~1.21%, P2O5 4.31~4.41%, TiO2 1.71~1.81%, and Cr2O3 0.02~0.12%.

Citation Information

Patent Citations

  • Method for preparing CO-rich gas through petroleum coke catalytic gasification

    CN108485708A